Synergetic Effect of Digestate Dissolved Organic Matter and Phosphogypsum Properties on Heavy Metals Immobilization in Soils - Skvortsova P. O.; Ablieieva I. Yu.; Tonderski K.; Chernysh Ye. Yu.; Plyatsuk L. D.; Sipko I. O.; Mykhno H. I. (Журнал інженерних наук)
The main idea was to justify the natural, technological, and ecological aspects of digestate-based composite for heavy metals (HMs) binding in soil due to organic matter content and mineral additives’ biosorption properties. The study aimed to determine the potential of a composite made from digestate and phosphogypsum for remediation of HMs polluted soils and the role of dissolved organic matter (DOM) in binding HMs. Methods used included a literature review to identify the mechanisms for HM binding to digestate DOM, a laboratory setup for producing a digestate-based composite with digestate (from manure or sewage sludge) mixed with phosphogypsum, and an analysis of digestate fluorescence properties. Results show that a composite based on digestate from manure as feedstock had a higher fluorescence complexity index than a composite with sewage sludge digestate (2.2 and 1.71, respectively). However, the DOM stability in the sewage sludge digestate composite was higher than reported in the literature, probably due to the mineral composition of phosphogypsum, which resulted in a high HMs sorption capacity and its positive effect on soil microbial activity. Based on the theoretical substantiation of DOM content and its binding properties, manure was the most effective feedstock type out of the two tested if digestate was used for HM remediation. Using a digestate-based composite with phosphogypsum can potentially reduce the ecological risk levels imposed by HM-contaminated soils from considerably too low.